2020
DOI: 10.1210/clinem/dgaa441
|View full text |Cite|
|
Sign up to set email alerts
|

Approach to the Patient: Perioperative Management of the Patient with Pheochromocytoma or Sympathetic Paraganglioma

Abstract: Abstract Pheochromocytomas and sympathetic paraganglioma (PPGL) are rare chromaffin cell tumors originating in the adrenal medulla and sympathetic paraganglia, respectively, which share the capacity to synthesize and release catecholamines. The incidence of PPGL has increased in recent years. Surgical resection is the only curative treatment for PPGL. Management of patients with PPGL is complex and should be done by a specialized multidisciplinary team in centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 138 publications
0
45
0
3
Order By: Relevance
“…Current guidelines suggest that in order to normalize BP of PCC patients, the preoperative medication should be initiated 7 to 14 days before surgery, and adrenergic blockade is recommended as the first choice mostly ( 1 , 8 ). Liu et al ( 13 ) reported that preoperative adrenergic blockade treatment duration ≤ 14 days was a risk factor of massive hemorrhage in PCC surgery and increased RBC transfusion rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines suggest that in order to normalize BP of PCC patients, the preoperative medication should be initiated 7 to 14 days before surgery, and adrenergic blockade is recommended as the first choice mostly ( 1 , 8 ). Liu et al ( 13 ) reported that preoperative adrenergic blockade treatment duration ≤ 14 days was a risk factor of massive hemorrhage in PCC surgery and increased RBC transfusion rate.…”
Section: Discussionmentioning
confidence: 99%
“…Pheochromocytoma (PCC) is a catecholamine secreting tumor arising from chromaffin cells of the adrenal medulla. Circulating catecholamines cause a series of clinical symptoms such as elevated blood pressure, palpitation, headache, as well as heart, brain, kidney and other organ complications ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary goals of the preoperative treatment of pheochromocytomas and sympathetic PGLs are to normalize BP and HR, restore cardiac volume depletion, and avoid the risk of a catecholaminergic storm and its negative consequences on the cardiovascular system induced by surgery. The objectives of the preoperative treatment are [1,43]:…”
Section: Presurgical Treatmentmentioning
confidence: 99%
“…Before surgery, current recommendations include management with alpha-blockers and volume expansion using saline, aiming to prevent hemodynamic intraoperative complications during surgery derived from a massive catecholamine release while the tumor is in situ and a marked blood pressure fall that starts when large veins are sectioned. In 2014, our center started a preoperative protocol similar to one recently published [ 20 ] that also involves monitoring patient blood pressure/electrocardiogram/glucose during and after surgery via arterial catheters. We found fewer hypertensive crises over the past decade, compared with similar cohorts that did not apply such preparation protocols [ 21 ].…”
Section: Discussionmentioning
confidence: 99%